T cell response to anti-CD3 antibody in Down's syndrome. Issue 11 (November 1987) - Bertotto, A; Arcangeli, C; Crupi, S; Marinelli, I; Gerli, R; Vaccaro, R
Abstract : The non-specific mitogen phytohaemagglutinin (PHA) and an anti-CD3 (OKT3) monoclonal antibody were used to measure the lymphocyte proliferative response in blood samples from 15 subjects with Down's syndrome. Blood from 15 healthy controls closely matched for age and sex was also assayed. The mean blastogenic value in PHA stimulated patient lymphocyte cultures was similar to that calculated in the controls. In contrast, the mitogenic response of lymphocytes from patients with Down's syndrome to anti-CD3 stimulation was on average significantly reduced. Immunofluorescence studies and additional experiments carried out by using semiallogeneic (maternal) monocytes as a source of antigen presenting cells showed that the impaired anti-CD3 induced mitogenesis in Down's syndrome could not be ascribed either to a lack of binding of the antibody to the trisomic cells, or to a defective monocyte-T cell interaction. These findings help to explain the cellular basis of the immune defect in Down's syndrome.